On the collapse of cotton/epoxy tubes under axial static loading - Mahdi, E.; Hamouda, A. M. S.; Sahari, B. B.; Khalid, Y. A. (Springer, 2003)
Experimental quasi-static crushing tests and finite element analysis have been carried out for unidirectional filament wound laminated cotton/epoxy tubes. The work focuses on three main factors, which considerably affect the axial collapse load of unidirectional natural composite tubes. These factors are structural geometry, fibre diameter and fibre orientation. Cotton/epoxy tubes with different diameters (50, 70, 90, 110 and 130 mm) were examined and tested. The fibre orientation angles were 80 and 90°. The initial geometric imperfections are measured using the computerised Mistral coordinate measuring machine. The numerical prediction was obtained using commercially available finite element software. A limited agreement between the experimental and computational results was obtained. For all structures considered classical axial collapse eigenvalues were computed. The initial failure crush load computed from the finite element simulation model has been compared with the experiments.